Pengaruh Brand Loyalty dan Perceived Quality terhadap Kepuasan Pembelian - Wasil, Mohammad (FORUM EKONOMI, 2017)
Brand Loyalty and Perceived Quality toward the Satisfaction of Purchasing Samsungs Android-Based Galaxy Handphones. This research aims to find out and to analyze the influence of Brand Loyalty and Perceived Quality toward the Satisfaction of Purchasing Samsungs Android-Based Galaxy Handphones and to find out which one from the two variables of Brand Loyalty and Perceived Quality has the most dominant influence on the satisfaction of purchasing Samsungs Android-Based Galaxy handphones by the students of Faculty of Economy, Mulawarman University, Samarinda. The theory underlying this research is Marketing Management by using Multiple Linear regression. Based on the result og analysis and discussion, it can be concluded in this research that: Y = 6,224 + 0,141 X1 + 0,377 X2. The result of analysis revealed that there was simultaneous significant of influence of Brand Loyalty and Perceived Quality on the satisfaction of purchasing Samsungs Android-Based Galaxy handphones and the most dominant influence on the satisfaction of purchasing Samsungs Android-Based Galaxy handphone by the students of Faculty of Economy, Mulawarman University, Samarinda was Perceived Quality Variable. The first hypothesis that was proposed by the researcher was accepted and statistically proven, while the second hypothesis was not accepted and statistically unproven.Keywords: Brand Loyalty, Perceived Quality, Consumer Gratification, Static Tradeoff Theory